2000
DOI: 10.1053/rmed.2000.0808
|View full text |Cite
|
Sign up to set email alerts
|

Neither IL-1 β, IL-1 receptor antagonist, nor TNF- α polymorphisms are associated with susceptibility to COPD

Abstract: The cytokines that contribute to airway inflammation, including interleukin-1beta (IL-1beta) and tumour necrosis factor alpha (TNFalpha), might have key roles in the development of chronic obstructive pulmonary disease (COPD). Interleukin-1 receptor antagonist (IL-1RN), the physiological antagonist of IL-1beta, is also known to play a crucial role in several chronic inflammatory diseases. In this study, we investigated the association of the polymorphisms of IL-1beta, IL-1RN and TNFalpha with susceptibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 31 publications
2
55
0
5
Order By: Relevance
“…Working on this assumption and given the lack of association of allele 2 of the TNF-308 (TNF-308*2) with COPD in another Japanese study [16], and the findings of KEATINGS et al [17] who identified a COPD phenotype, i.e. poor prognosis possibly associated with the same allele in the British population, the present authors decided to re-evaluate the role of the TNF family genes in the Italian COPD population.…”
mentioning
confidence: 99%
“…Working on this assumption and given the lack of association of allele 2 of the TNF-308 (TNF-308*2) with COPD in another Japanese study [16], and the findings of KEATINGS et al [17] who identified a COPD phenotype, i.e. poor prognosis possibly associated with the same allele in the British population, the present authors decided to re-evaluate the role of the TNF family genes in the Italian COPD population.…”
mentioning
confidence: 99%
“…The IL1B gene contains an SNP in the promoter region (C-511T) and the IL1RN gene contains a pentaallelic tandem-repeat polymorphic site in intron 2. None of the genotypes alone were associated with the susceptibility to COPD, nor with the rate of decline of lung function in smokers (Ishii et al 2000). However, the distribution of IL1B/IL1RN haplotypes differed in smokers with a rapid decline in lung function from non-decliners (Joos et al 2001).…”
Section: Interleukinesmentioning
confidence: 83%
“…Their results indicated that the TNF-α-308 allele 2 might be partly associated with the emphysematous phenotype (Sakao et al 2002). In contrast, associations between the TNF2 allele and COPD were not confirmed in other studies, neither in Caucasians (Higham et al 2000;Patuzzo et al 2000), nor in a Japanese population (Ishii et al 2000) (Table 3). There was no association between the TNF-α gene promoter genotype and the severity of airflow obstruction or the degree of emphysema in COPD (Higham et al 2000), neither this genotype played a significant role in bronchiectasis developing as a consequence of frequent respiratory tract infections in COPD patients (Patuzzo et al 2000).…”
Section: Gene Polymorphisms Of Inflammatory Mediators In Relation To mentioning
confidence: 85%
“…Genotyping (adapted after Ishii T et al 2000) [19] DNA was extracted from 300 μl peripheral blood samples using Wizard Genomic DNA Purifi cation Kit (Wizard® Genomic DNA Purifi cation Kit, Promega, MA, USA).…”
Section: Methodsmentioning
confidence: 99%